Hypoxic conditions alter developing branchial arch-derived structures in zebrafish - Trish E Parsons; Seth M Weinberg; Michael Tsang; Alexandre R Vieira (University Library System, University of Pittsburgh, 2014)
Background: Previous epidemiological findings have implicated hypoxia as a risk factor for craniofacial defects including cleft lip, microtia and branchial arch anomalies. This study tests the hypothesis that hypoxic exposure results in craniofacial shape variation in a zebrafish model. Methods: Three sets of zebrafish embryos were raised in uniform conditions with the exception of dissolved oxygen level.  At 24 hours past fertilization (hpf) embryos were placed in hypoxic conditions (70% or 50% dissolved oxygen tank water) and compared to unexposed control embryos.  After 24 hours of exposure to hypoxia, the embryos were incubated under normoxia.  Larvae were collected at 5 days post fertilization (dpf) and stained for cartilage. Images were taken of each specimen and subsequently landmarked to capture viscerocranial morphology.  A geometric morphometric analysis was performed to compare shape variation across groups. Results: The mean branchial arch shape of each exposure group was significantly different from controls (p<0.001).  Principal components analysis revealed a clear separation of the three groups, with controls at one end of the shape spectrum, the 50% hypoxia group at the other end, and the 70% hypoxia group spanning the variation in between. Conclusions: This experiment shows that hypoxia exposure at 24hpf is capable of affecting craniofacial shape in a dose-dependent manner.  These results may have implications not only for high altitude fetal health, but other environments, behaviors and genes that affect fetal oxygen delivery.